2017
DOI: 10.1371/journal.pone.0180431
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal parasite infections and self-medication in wild chimpanzees surviving in degraded forest fragments within an agricultural landscape mosaic in Uganda

Abstract: Monitoring health in wild great apes is integral to their conservation and is especially important where they share habitats with humans, given the potential for zoonotic pathogen exchange. We studied the intestinal parasites of wild chimpanzees (Pan troglodytes schweinfurthii) inhabiting degraded forest fragments amid farmland and villages in Bulindi, Uganda. We first identified protozoan and helminth parasites infecting this population. Sixteen taxa were demonstrated microscopically (9 protozoa, 5 nematodes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 95 publications
(160 reference statements)
1
32
0
Order By: Relevance
“…It could be that strongyle infection makes the large intestine a more suitable environment for commensal protozoa. It has been observed in chimpanzees that a positive correlation between intestinal parasites and commensal protozoa arose from complex interactions mediated by the host immune response and competition among taxa (McLennan et al, 2017 ). In horses, Güiris et al ( 2010 ) have shown that helminths cohabit with commensal protozoa in the gastrointestinal tract in natural conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It could be that strongyle infection makes the large intestine a more suitable environment for commensal protozoa. It has been observed in chimpanzees that a positive correlation between intestinal parasites and commensal protozoa arose from complex interactions mediated by the host immune response and competition among taxa (McLennan et al, 2017 ). In horses, Güiris et al ( 2010 ) have shown that helminths cohabit with commensal protozoa in the gastrointestinal tract in natural conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Data are limited because sampling is largely based on fecal analysis, which requires consecutive samplings of the same individual (Muehlenbein and Watts 2010) and because of infections introduced by human intrusions and habitat degradation with expanded farming and exposure to domestic animals (McLennan et al 2017). We must assume that all sampled chimpanzee populations have had direct or indirect exposure to transmissible pathogens from humans and domestic animals.…”
Section: Bipedality Lung Evolution and Aerosol Exposuresmentioning
confidence: 99%
“…In NHPs, patterns of gut-eukaryotic load are modulated by host behavior including social structure, grooming, and parasite avoidance behaviors [5,9,84,85], proximity to humans and other sources of transmission [86][87][88], and ecological factors (e.g., wet versus dry season) [89]. Assessing the relative contribution of these factors to variation in gut-eukaryotic load across NHPs in this study is beyond the scope of the current dataset but these are important considerations for future comparative research.…”
Section: Distribution Of Gut-associated Eukaryotes Within and Across mentioning
confidence: 99%